Baldric of Bourgueil : 'history of the Jerusalemites' : a translation of the 'Historia Ierosolimitana' /: 'history of the Jerusalemites' : a translation of the 'Historia Ierosolimitana'. (2020) - of Bourgueil, Archbishop of Dol, Baudry, 1046-1130
No abstract available